Developing a food safety system from a farmer network in Sikhio district, Nakhon Ratchasima Province - โพธิพิมพ์ มะลิ; Khetbumrung, Valanchaya; Phinyo, Phongphat; Aeksanti, Thawatchai (Journal of Vongchavalitkul university, 2020)
This participatory action research aimed to develop a food safety system from the network of farmers in Sikhio district, Nakhon Ratchasima Province. The purposive sampling was used for participants whose representatives of government agencies, private sector, community leaders and farmers, 32 persons. The research instrument consisted of in-depth interview, questionnaires and workshop (8 steps in the modification of the constitution health). Quantitative data were analyzed by using descriptive statistics and qualitative data were analyzed by using content analysis. The results shown that most of the farmers have lived in the agricultural area since birth, Have own land, Use rainwater for farming, Drought problem. Loans for investment in agriculture. They have a high level of knowledge and understanding about organic agriculture and the environment. There was a moderate level of practice while doing agriculture. The overall problem found that chemicals was used in vegetables garden, Lack of water sources for farming, Lack of strong and continuous integration, Lack of food safety stores also sell illegal chemicals. All farmers couldn’t to deliver enough and continuous products to the hospital. Food safety system adopted divided according to the relevant groups into 3 groups as follows: 1) Farmers groups must join together to exchange knowledge in the form of peers to help friends develop knowledge and skills in food safety production. Government agencies have to support them about development and the inspection of agricultural product safety standards. 2) Product group have to set up a database system for producers, consumers, distribution points, and public relations for effective food safety system network connections in all groups and develop standard packaging product. 3) Consumer group have to develop knowledge about nutrition and buying food from food safety sources. Keywords: Developing, food safety system, farmer